2010
DOI: 10.1002/ijc.25085
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of hyaluronan production by CD44 positive glioma cells

Abstract: SUMMARY This study examines the functional relationship between glioma cell production of hyaluronan (HA), known to play a role in glioma invasion, expression of its CD44 receptor, and glioma cell viability. Production of HA by CD44 positive mouse G26 and human U373 glioma cell lines was evaluated and compared to that of a CD44 positive mouse fibroblast-like L929 cell line. We found that both G26 and U373 MG glioma cells, but not L929 fibroblast-like cells, synthesized HA. HA synthesis by glioma cells was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 70 publications
1
28
0
2
Order By: Relevance
“…It was observed that full length, large size HA had an antiangiogenic property, whereas smaller oligosaccharides after degradation (3-10 disaccharide units) were no longer anti-angiogenic (Deed et al 1997). We found that small size oligosaccharide, decamer HA-10, exogenously added to the cell culture stimulated HA production by glioma cells (Wiranowska et al 2010), as previously described for normal human fibroblasts (Luke and Prehm 1999). These authors found that displacement of nascent HA from the receptors by HA oligosaccharides led to stimulation of HA synthesis (Luke and Prehm 1999).…”
Section: Extracellular Matrix Molecules In Glioma 341 Glycosaminoglmentioning
confidence: 67%
See 1 more Smart Citation
“…It was observed that full length, large size HA had an antiangiogenic property, whereas smaller oligosaccharides after degradation (3-10 disaccharide units) were no longer anti-angiogenic (Deed et al 1997). We found that small size oligosaccharide, decamer HA-10, exogenously added to the cell culture stimulated HA production by glioma cells (Wiranowska et al 2010), as previously described for normal human fibroblasts (Luke and Prehm 1999). These authors found that displacement of nascent HA from the receptors by HA oligosaccharides led to stimulation of HA synthesis (Luke and Prehm 1999).…”
Section: Extracellular Matrix Molecules In Glioma 341 Glycosaminoglmentioning
confidence: 67%
“…We showed previously that blocking CD44 and interfering with HA-CD44 ligand-receptor interaction resulted in inhibition of glioma cell invasion, decreased HA production and led to glioma cell apoptosis (Wiranowska et al 1998, Wiranowska et al 2010. In addition, recent data by Xu et al showed that CD44 attenuates activation of the Hippo signaling pathway and that knockdown of CD44 expression resulted in the inhibition of glioblastoma.…”
Section: Targeting Ha and Cd44 Adhesion Moleculementioning
confidence: 93%
“…The main component of brain ECM is the polysaccharide hyaluronic acid (HA) [20,21], which is a glycosaminoglycan made up of repeating disaccharides of D-glucuronic acid and N- acetyl-D-glucosamine. HA is constitutively produced within GBM tumors, [22,23] and its abundance is associated with cell proliferation and infiltration. Its cellular receptor CD44 is also overexpressed in GBM, and cells containing CD44 localize to the normal brain-tumor interface in vivo, suggesting that CD44-enriched cells are more efficient at invading the brain parenchyma [24,25].…”
Section: Role Of Microenvironment In Gbm Progressionmentioning
confidence: 99%
“…The HA receptor CD44 adhesion molecule, is highly expressed on the leading edge of glioma at the interface with the normal brain tissue signifying the importance of these ECM molecules in glioma invasion [13,15,17,18,20,21]. It was found recently that HA and its CD44 receptor may play an important role in the "stemness" and survival of cancer stem cells [4].…”
Section: Forewordmentioning
confidence: 99%
“…All of these molecules play important roles in cell signaling and migration [16]. In addition, HA was recognized as main ECM component that forms a microenvironment in which stem cells can undergo self-renewal [4].The HA receptor CD44 adhesion molecule, is highly expressed on the leading edge of glioma at the interface with the normal brain tissue signifying the importance of these ECM molecules in glioma invasion [13,15, 17, 18, 20, 21]. It was found recently that HA and its CD44 receptor may play an important role in the "stemness" and survival of cancer stem cells [4].…”
mentioning
confidence: 99%